Dreaming of distant lands. How Fascism built colonial women (1937-1941) - Cagnolati, Antonella (Historia y Memoria de la Educación, 2022)
When they seized power in 1922, the Fascists adopted a patriarchal stance regarding women. Adopting the pronatalist theories of Riccardo Korherr, Federico Marconcini and Ferdinando Loffredo, Fascism became a staunch defender of demographic policies relegating women exclusively to the role of wife and mother, mere breeding machines whose only job was to increase the number of Italians for the war effort and to drive colonial expansion in order to keep up with the other European nations. As a consequence of the war for the conquest of empire in East Africa, a population management strategy was conceived in which young women would be sent to produce families to re-populate Ethiopia in the name of the Fascist state. Accordingly, it became necessary to develop a different model for educating young women, to actively equip them for their new lives in Africa. With this in mind, the Fascist leadership exploited women’s Fascist associations, drawing up national curricula for standardized training of these before sending them off to Africa. This investigation explores the contemporary press such as L’Azione Coloniale and the training manual used in the courses preparing women for life in the African colonies. The objective was to understand whether the change in the educational policy devised for a group of young women, chosen for convenience, may have modified the overall image of women on a symbolic level in the last years of the regime.